Rat-bite fever due to Streptobacillus notomytis isolated from a human specimen. Issue 4 (April 2018) - Fukushima, Kazuaki; Yanagisawa, Naoki; Imaoka, Koichi; Kimura, Masanobu; Imamura, Akifumi
Abstract: Rat-bite fever (RBF) is a disease that usually presents with fever, arthralgia and skin rash. Streptobacillus moniliformis was considered the main cause of RBF among the genus Streptobacillus . Although with similar clinical presentation, RBF due to Streptobacillus notomytis is unusual in humans. To the best of our knowledge, we present a case involving the first isolate of S. notomytis in humans. A 63-year-old woman was admitted to our hospital with fever, rash and polyarthritis. She recalled being bitten by a rat on her finger 5 days before presentation. Clinical manifestations were compatible with rat-bite fever (RBF) and the diagnosis was confirmed by the detection of Streptobacillus species from both blood and pustule samples. Initial polymerase chain reaction tests revealed that the organism was S. moniliformis . However, thorough genetic analysis revealed the organism to be S. notomytis . The condition was successfully treated with ampicillin.